Developing a national salt reduction strategy for Mongolia - Enkhtungalag, Batsaikhan (Cardiovasc Diagn Ther, 2015)
BACKGROUND: The increase in prevalence of risk factors such as hypertension has contributed to an incremental rise in non-communicable diseases (NCDs) in Mongolia over recent decades, such that they now account for 80% of all deaths in the country. Salt reduction is one of the most cost-effective interventions to reduce the burden of NCDs. METHODS: In 2011, the Ministry of Health (MOH) instigated the development of a national salt reduction strategy for Mongolia. As part of a 2-week national consultation and training program on salt reduction, it established an inter-sectoral working party and organized a series of bilateral meetings and visits to factories. Actions arising included a baseline survey of population salt consumption patterns and the implementation of a series of pilot salt reduction initiatives. RESULTS: The results of the baseline assessment revealed that average daily intake of salt, based on 24 hour urine samples from a representative national sample (n=1,027), was 11.06±5.99 g in 2011, more than double the World Health Organization (WHO) five grams recommendation. Moreover, while most participants knew that salt was bad for health, few were taking efforts to reduce intake, and many were consuming highly salty meals and tea; salt in tea alone was estimated to contribute 30% of daily salt intake. A pilot Pinch Salt intervention to reduce salt consumption of factory workers was undertaken in Ulaanbaatar (UB) city between 2012 and 2013, and was associated with a reduction of 2.8 g of salt intake. Ongoing food industry initiatives have led to significant reductions in salt levels in bread, and companies producing processed meat have indicated a willingness to reduce salt. Relevant stakeholders have also supported the campaign by participating in annual World Salt Awareness Week events. The activities to date have demonstrated the potential for action and there is now a need scale these up to a national level to ensure that Mongolia is in a strong position to achieve a 30% reduction in population salt intake by 2025. The main goal of the Mongolian national salt reduction strategy is to create a social, economic and legal environment that supports salt reduction, including by influencing food supply, increasing partnerships between government and relevant stakeholders, and creating an enabling environment to support improved consumer choices. The strategy will be implemented from 2015 to 2025, with an interim review of progress in 2020. CONCLUSIONS: Given that Mongolia has one of the highest rates of stroke in the world, which is strongly associated with population-wide blood pressure (BP) levels, the addition of a population-based stroke surveillance program would provide a reliable direct assessment of the impact of these salt reduction initiatives on the health of the Mongolian people. The results from this research would likely be widely generalizable to other populations experiencing similar lifestyle transitional changes.